2023
DOI: 10.3390/agronomy13061466
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Chemical and Organic Fertilization Differently Affect Soil Aggregates and Associated Carbon and Nitrogen in the Loess Plateau of China

Abstract: Fertilizer sources may have variable effects on soil aggregation, aggregated-associated C and N, and wheat yield. A 34-year field experiment was performed to evaluate the influences of chemical and organic fertilization on soil aggregates and associated carbon and nitrogen under winter wheat in a Cumulic Haplustoll of the Loess Plateau, China. Treatments included unfertilized control (CK), inorganic N fertilizer (NF), inorganic P fertilizer (PF), inorganic N and P fertilizer (NP), organic manure (M), inorganic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Organic C and N turnover and mineralization rates are significantly different in soil aggregates of different particle sizes [7]. It was shown that C and N sequestration in soils was related to the size of aggregates and was mainly influenced by larger aggregates, and the improvement of soil structure was associated with an increase in SOC and TN, which were positively correlated with R 0.25 and MWD [8,9]. Moreover, SOC is more stable in aggregates of <2000 µm in diameter than in those of 2000-6300 µm, while N is more stable in aggregates of 2000-6300 µm than in those of <2000 µm [10].…”
Section: Introductionmentioning
confidence: 97%
“…Organic C and N turnover and mineralization rates are significantly different in soil aggregates of different particle sizes [7]. It was shown that C and N sequestration in soils was related to the size of aggregates and was mainly influenced by larger aggregates, and the improvement of soil structure was associated with an increase in SOC and TN, which were positively correlated with R 0.25 and MWD [8,9]. Moreover, SOC is more stable in aggregates of <2000 µm in diameter than in those of 2000-6300 µm, while N is more stable in aggregates of 2000-6300 µm than in those of <2000 µm [10].…”
Section: Introductionmentioning
confidence: 97%
“…Soil organic carbon content is also associated with microbial gene abundance, biomass, and biological activity [11]. Increasing soil organic carbon content can effectively promote the formation of organic-inorganic aggregates and thereby reduce the content of gravel in the soil [12]. The increase in soil water-holding capacity and bulk density is conducive to the accumulation of inorganic nutrients and soil organic carbon [13].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study demonstrated that with equal total nitrogen inputs, the replacement of 50% to 100% chemical fertilizers with organic fertilizers increased survival by 26.47% to 34.16%, yield by 63.2% to 156.6%, and nitrogen utilization rate by 16.5% to 18.5% in watermelon plants, compared to chemical fertilizers alone [11]. Numerous studies have found that organic fertilizers and the long-term application of combined organic and chemical fertilizers can increase soil organic matter content, promote the formation of macroaggregates [12,13], improve microbial biomass and accelerate microbial metabolism and reproduction [14,15], and enhance the activity of various enzymes in the soil and its agglomerates [16,17]. However, variations in soil microbial communities are closely linked to crop species and the soil environment, and the effects of soil physicochemical properties (pH, salinity, carbon content, availability of nutrients, soil type, etc.)…”
Section: Introductionmentioning
confidence: 99%